The evolution of clinical skills peer teaching at the Faculty of Medicine, University of Maribor - Petra Rižnik; Sebastjan Bevc (Acta Medico-Biotechnica, 2021)
The Faculty of Medicine at the University of Maribor is the younger of the two medical faculties in Slovenia. Since its foundation, it has been successfully engaging students in the educational process. The result of students ´ involvement is the introduction of peer teaching, and along with that, the incorporation of objective structured clinical examination (OSCE) as an assessment method. This paper focuses on the development of clinical skills peer teaching and its accompanying tool of assessment, OSCE, at the Faculty of Medicine, University of Maribor.